"I Felt Powerful": Imagining Re-existence Through an Embodied Fugitive Pedagogy for Mexican American/Latinx Teachers. Issue 2 (3rd April 2021) - Caldas, Blanca
ABSTRACT: This study shows how a cohort of 22 bilingual preservice teachers imagined re-existence through fugitivity by using embodiment as a decolonial pedagogy to contest linguistic, xenophobic, racist, and classist oppression at micro levels at schools. The participants dramatized their future selves in specific situations they feared to encounter, and conjured their desire to become agents of change and to escape from feelings of being overwhelmed and disempowermed. The purposeful pedagogical shifts during the course (through the use of counterstories as legitimate texts, the centrality of the body through drama-based pedagogies, and the use of translanguaging as the language of instruction) facilitated the students' imagining and transforming traditional scripts and producing their own skits, which tackled compelling issues they might encounter, at schools pertaining to bilingual education. The four self-generated scripts created and performed in class portrayed the teacher advocate-protagonist in dialogue with peers, parents, and administrators defending the language rights of the students. The participants enacted their scripts, highlighting the role of the advocate teacher in action and supporting the use of multiple language practices, the implementation of additive bilingual programs, the increase of resources for better materials in Spanish, and the training of mainstream teachers to be linguistically and culturally responsive. The scripts showcased are examples of the crafting of participants' tactics to engage in re-existence to subvert dominant discourses and ideologies to provide equitable education for culturally and linguistically minoritized students and families and imagine other ways of being, feeling, teaching, and learning for excellence on their terms.